Characterization of lncRNA–miRNA–mRNA Network to Reveal Potential Functional ceRNAs in Bovine Skeletal Muscle - Yue, Binglin; Li, Hui; Liu, Mei; Wu, Jiyao; Li, Mingxun; Lei, Chuzhao; Huang, Bizhi; Chen, Hong (Frontiers in Genetics, 2019)
There is growing evidence that non-coding RNAs are emerging as critical regulators of skeletal muscle development. In order to reveal their functional roles and regulatory mechanisms, we constructed a lncRNA–miRNA–mRNA network according to the ceRNA(competitive endogenous RNA) theory using our high-throughput sequencing data. Subsequently, the network analysis, GO(Gene Ontology) analysis, and KEGG(Kyoto Encyclopedia of Genes and Genomes) pathway analysis were performed for functional annotation and exploration of lncRNA ceRNAs. The results uncovered a scale-free characteristics network which exhibited high functional specificity for bovine skeletal muscle development: co-expression lncRNAs were significantly enriched in muscle development related biological processes and Wnt signaling pathway. Further more, GSEA(Gene Set Enrichment Analysis) indicated that the risk score gets the tendency to associate with myogenesis, and differentially expressed RNAs were validated by qPCR, further confirming the credibility of our network. In summary, this study provides insights into lncRNA-mediated ceRNA function and mechanism in bovine skeletal muscle development and will expand our understanding of lncRNA biology in mammals.